Evaluation of The Operational Performance and Maintenance of Valves In Biodiesel Plant - ALIAS, AHMAD FAEIZ HAFIZIE; Ibrahim, Md Zin (Progress in Engineering Application and Technology, 2021)
This research about to evaluate the operational performance and do maintenance of valves in biodiesel plant. This paper discuss the performance of valve by observe the flowrate at the main pipe. After do an observation, the selected valve will be maintenance. An experiment was conducted with do maintenance at two butterfly valve in different area. The experimental result was evaluated by observe the flowrate gauge and pressure gauge reading and compare before maintenance and after maintenance. The result shows the flowrate for V101 can be increase for 50 percent by do maintenance from 160.25m3/s to 240.37 m3/s. For the V201, flowrate also increase from 12m3/h to 18 m3/h where approximately 50 percent increasing after do maintenance and to the optimum value. The valve can extend their life expectancy and can be use for many years with the excellent performance.